Integrating Economic Theory into Hydropower Project Evaluation: A Conceptual Review (DEPAN, 2025)
This study examines the ethical implications of Cost-Benefit Analysis (CBA) in evaluating large-scale hydropower projects, with a particular focus on the challenges posed by traditional utilitarian frameworks. While CBA is widely used for policy decision-making, it often fails to account for distributional equity, particularly among marginalized communities and future generations. This research highlights key shortcomings, including the tendency of CBA to favor wealthier groups due to income-based willingness-to-pay metrics, as well as its failure to incorporate non-market environmental values such as cultural, aesthetic, and ecological considerations. The study also explores the limitations of standard discounting practices that undervalue long-term environmental and social benefits, leading to intergenerational inequity. By proposing a pluralistic approach that integrates utilitarianism, egalitarianism, and environmental ethics, the study calls for a more comprehensive and inclusive evaluation framework for development projects. This approach would not only enhance the fairness and inclusivity of decision-making but also promote sustainability by recognizing the intrinsic value of environmental and cultural resources. The findings suggest that CBA should be viewed as a decision-support tool, rather than a definitive guide, and should be complemented with qualitative assessments, stakeholder engagement, and value-based judgments for better policy outcomes.